Implementasi Aplikasi Jual Beli Pakaian Bekas Sebagai Solusi Ramah Lingkungan - Nurannas; Imam Muslem; Hannan Asrawi (Fakultas Ilmu Komputer Universitas Almuslim, 2026)
The increasing growth of fashion trends has encouraged people to purchase clothing more frequently, resulting in a higher number of unused garments and textile waste. Many second-hand clothes are still suitable for reuse, either through resale or donation, but their management is often conducted conventionally through social media, private messages, or direct transactions. This condition causes product data, transaction records, stock information, payment status, delivery information, and donation data to be less organized. This study aims to implement a web-based second-hand clothing buying, selling, and donation application as an environmentally friendly solution. The application was developed using PHP as the programming language and MySQL as the database management system. The system involves three main actors, namely admin, seller, and buyer. The main features include user registration, login, product management, marketplace, product detail, shopping cart, checkout, payment recording, delivery management, and donation management. System testing was carried out using the black-box testing method by observing the suitability between input, process, and expected output for each feature. The testing results show that all main features run according to their expected functions. Therefore, this application can support the reuse of second-hand clothing, facilitate structured online transactions, improve data management, and encourage social and environmental awareness through an integrated donation feature.